Socio-Demographic changes in Bangladesh: a study on impact - Khan, H.T. Abdullah; Raeside, Robert (BRAC University, 2010)
The paper aims at examining the socio-demographic changes over years and their impact on the future age-sex structure of population in Bangladesh. The mechanisms of change in the population are reviewed and it is shown that success in reducing fertility will alter the profile of the dependent population potentially to the benefit of Bangladesh. The study demonstrates that a large portion of population is still under age of 15 years and this youth bulge will contribute to the country's future reproduction and that to accommodate this progress in economic development is a necessity. Finally, the paper briefly lays out some policy implications.